Introducing the national COPD resources and outcomes project - Pursey Nancy A; Buckingham Rhona J; Lowe Derek; Harrison Brian DW; Stone Robert A; Hosker Harold SR; Potter Jonathan M; Roberts C Michael (BMC, 2009)
Abstract Background We report baseline data on the organisation of COPD care in UK NHS hospitals participating in the National COPD Resources and Outcomes Project (NCROP). Methods We undertook an initial survey of participating hospitals in 2007, looking at organisation and performance indicators in relation to general aspects of care, provision of non-invasive ventilation (NIV), pulmonary rehabilitation, early discharge schemes, and oxygen. We compare, where possible, against the national 2003 audit. Results 100 hospitals participated. These were typically larger sized Units. Many aspects of COPD care had improved since 2003. Areas for further improvement include organisation of acute care, staff training, end-of-life care, organisation of oxygen services and continuation of pulmonary rehabilitation. Conclusion Key Points: positive change occurs over time and repeated audit seems to deliver some improvement in services. It is necessary to assess interventions such as the Peer Review used in the NCROP to achieve more comprehensive and rapid change.